2011
DOI: 10.1007/s11596-011-0691-x
|View full text |Cite
|
Sign up to set email alerts
|

Intensity-modulated radiotherapy for sinonasal teratocarcinosarcoma

Abstract: Surgical excision and postoperative radiotherapy are widely accepted therapeutic modalities for sinonasal teratocarcinosarcoma (SNTCS). Previous studies have shown that intensity-modulated radiation therapy (IMRT) is safe and effective for the treatment of some sinonasal malignancies. We hypothesize that use of IMRT for SNTCS may result in clinical benefits. We report here two cases of SNTCS that were treated by IMRT. One patient was given extensive IMRT involving elective neck irradiation. Follow-up examinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…and Peng et al . have utilized IMRT with good effect, with no recurrence at 2 and 3.5 years respectively [10, 11]. Our case supports the use of IMRT given the excellent outcome in our patient with minimal side effects 2 years post-radiotherapy.…”
Section: Discussionsupporting
confidence: 77%
“…and Peng et al . have utilized IMRT with good effect, with no recurrence at 2 and 3.5 years respectively [10, 11]. Our case supports the use of IMRT given the excellent outcome in our patient with minimal side effects 2 years post-radiotherapy.…”
Section: Discussionsupporting
confidence: 77%
“…All these patients showed no further evidence of disease, with the longest follow-up at 372 months. 1 Similarly, Peng et al 29 reported on one patient who, after surgery plus radiation therapy, showed no recurrence or metastasis at up to 3.5 years after treatment. Takasaki et al 10 also reported on one patient whose follow-up examination at close to 3.5 years after surgery plus radiation therapy revealed no evidence of recurrence or metastasis.…”
Section: Discussionmentioning
confidence: 92%
“…A total of 62 original articles and two review articles meeting inclusion criteria were reported in the literature from 1977–2018 and included in the study, representing a total of 127 unique patients (Figure 1). 164 In addition to these reported cases, we also present two new cases of SNTCS treated at our institution with review of imaging, pathology and treatment outcome.…”
Section: Methodsmentioning
confidence: 96%